FICTION AS A MEANS OF EDUCATION BEHAVIORAL CULTURES OF OLDER PRESCHOOL CHILDREN - Nabiyeva Zarina Nabiyevna (Bright Mind Publishing, 2025)
The article touches on the topic of how fiction affects the education of the culture of behavior of older preschool children. Listening to the work, the child gets acquainted with the surrounding life, nature and the work of people. The artistic word affects not only the consciousness, but also the feelings and actions of the child.
Keywords: Fiction, pedagogical tools, education of the culture of behavior, book, fairy tale.